Radical Political Imagination and Generational Utopias: Gun Control as a Site of Youth Activism - Seppälä Mila (Brill, 2022)
This chapter explores radical political imagination in youth-led gun control advocacy groups in Texas, including the types of actions, activist subjectivities, and utopian visions for the future it has produced. It traces how the “absurdist direct action campaign” staged by a group of young women at the campus of The University of Texas at Austin in the fall of 2016 radically reimagined political action in the sphere of gun violence prevention. In the absence of political opportunities, the “Cocks not Glocks” protest used humor as a way to mitigate the precarious experiences and feelings of helplessness the Campus Carry law produced among certain segments of the campus community. Examining how radical imagination has been evoked in the Texas chapters of the national gun control movement March For Our Lives, the chapter discusses how a movement built upon an imagined generational community has led to a confluence of different issue-based groups, facilitating collective processes of imagining larger—even utopian—political projects that are uniquely “American” in nature. These examples of everyday resistance and broader collective action in Texas represent an important moment in the re-emergence of political hope among the Left in the United States that has been missing since “the Long Sixties.”
Up in Arms: Gun Imaginaries in Texas